Single arterial access for Ecpella and jugular venous cannulation provides full mobility on a status 1 heart transplant recipient - Macit Bitargil; Si Pham; Osama Haddad; Basar Sareyyupoglu (ESC Heart Failure)
Abstract Concomitant treatment with veno‐arterial extracorporeal membrane oxygenation (VA‐ECMO) and Impella may improve outcomes in patients with cardiogenic shock compared with VA‐ECMO alone. Here, we explain a new method to introduce Impella and ECMO through the same arterial access site and jugular venous cannulation to accomplish a mobile patient concept.